Transvenous embolization of a cerebrospinal fluid–venous fistula for the treatment of spontaneous intracranial hypotension. (14th October 2021) - Borg, Nicholas; Oushy, Soliman; Savastano, Luis; Brinjikji, Waleed
Abstract : Cerebrospinal fluid–venous fistula is an increasingly recognized cause of spontaneous intracranial hypotension. 1 The site of the leak is between the dural sleeve around a spinal nerve root and the surrounding foraminal veins. In appropriately investigated patients, transvenous embolization of the draining foraminal and paraspinal veins has been shown to be an effective way of treating the disease, with low periprocedural morbidity, improvement in symptoms and radiological appearances. 2 Video 1 shows the technique employed in a typical case using Onyx (Medtronic, Minnesota, USA) to embolize a CSF–venous fistula at the right T10 neural foramen.